Trap levels in graphene oxide : a thermally stimulated current study - Kajen, R. S. (2014)
We report thermally stimulated current (TSC) experiments on graphene oxide (GO) to study the effects of various defect levels near the GO Fermi level. The TSC peaks are ascribed to detrapping from defect levels to the GO hopping transport energy level, and are found to be in agreement with the GO density of states reported in the literature. This work will be useful in evaluating the use of GO in memory/dielectric/barrier applications.